2008
DOI: 10.1021/jp711554c
|View full text |Cite
|
Sign up to set email alerts
|

Hydration of Microcrystalline Cellulose and Milled Cellulose Studied by Sorption Calorimetry

Abstract: The hydration of two different polymorphs of microcrystalline cellulose (cellulose I and II), as well as the hydration of amorphous cellulose was studied using water sorption calorimetry, gravimetric water vapor sorption, nitrogen sorption, and X-ray powder diffraction. Amorphous cellulose was prepared by means of ball-milling of microcrystalline cellulose (MCC). Whereas X-ray data showed the untreated MCC to consist of cellulose I, the amorphous cellulose was found to recrystallize into cellulose II after con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(99 citation statements)
references
References 48 publications
5
92
1
1
Order By: Relevance
“…The reason for that was the presence of cellulosic filler and cellulose is a hydrophilic material which is well known for being able to absorb high amounts of water. In general, it is believed that, because of the contrasting sorption mechanisms (bulk for C II and surface for C I), less crystalline C II can adsorb more water than C I [47,48]. This relation can be seen for samples of CHT/5 C I and CHT/5 CII, but in our case it is no longer noticeable for composites with nanometric filler.…”
Section: Thermal Stability Of Compositesmentioning
confidence: 53%
“…The reason for that was the presence of cellulosic filler and cellulose is a hydrophilic material which is well known for being able to absorb high amounts of water. In general, it is believed that, because of the contrasting sorption mechanisms (bulk for C II and surface for C I), less crystalline C II can adsorb more water than C I [47,48]. This relation can be seen for samples of CHT/5 C I and CHT/5 CII, but in our case it is no longer noticeable for composites with nanometric filler.…”
Section: Thermal Stability Of Compositesmentioning
confidence: 53%
“…Kocherbitov et al evaluated the hydration of microcrystalline cellulose (cellulose I and II) and amorphous cellulose. They found that the water sorption increases from cellulose I to cellulose II to amorphous cellulose [73]. During the process of water absorption by amorphous cellulose, water molecules are first of all bound to the O6 and O2 hydroxyl groups of cellulose.…”
Section: Hygroexpansion Of Cellulosementioning
confidence: 99%
“…For celluloses that retain their native cellulose I crystal structures (which are the focus of this work), cellulose forms aggregates of microfibrils containing highly-ordered (crystalline) and less-ordered structures (Henriksson and Lennholm 2009). Moreover, cellulose ultrastructure affects hydration, as monolayer water mass depends on cellulose crystallinity indexes; and hydration affects ultrastructure, as water-filled pores collapse upon drying (Mihranyan et al 2004;Kocherbitov et al 2008). Nevertheless, in addition to such general properties, one also needs analytical techniques able to accurately and precisely measure material-specific ultrastructural parameters.…”
Section: Introductionmentioning
confidence: 99%